New dosimetric guidelines for linear Boltzmann transport equations through comparative evaluation of stereotactic body radiation therapy for lung treatment planning. Issue 12 (16th November 2021) - Webster, Matthew; Tanny, Sean; Joyce, Neil; Herman, Amy; Chen, Yuhchyau; Milano, Michael; Usuki, Kenneth; Constine, Louis; Singh, Deepinder; Yeo, Inhwan
Abstract: Purpose: To propose guidelines for lung stereotactic body radiation therapy (SBRT) when using Acuros XB (AXB) equivalent to the existing ones developed for convolution algorithms such as analytic anisotropic algorithm (AAA), considering the difference between the algorithms. Methods: A retrospective analysis was performed on 30 lung patients previously treated with SBRT. The original AAA plans, which were developed using dynamic conformal arcs, were recalculated and then renormalized for planning target volume (PTV) coverage using AXB. The recalculated and renormalized plans were compared to the original plans based on V100% and V90% PTV coverage, as well as V105%, conformality index, D2cm, Rx/Dmax, R50, and Dmin . These metrics were analyzed nominally and on variations according to RTOG and NRG guidelines. Based on the relative difference between each metric in the AAA and AXB plans, new guidelines were developed. The relative differences in our cohort were compared to previously documented AAA to AXB comparisons found in the literature. Results: AAA plans recalculated in AXB had a significant reduction in most dosimetric metrics. The most notable changes were in V100% (4%) and the conformality index (7.5%). To achieve equal PTV coverage, AXB required an average of 1.8% more monitor units (MU). This fits well with previously published data. Applying the new guidelines to the AXB plans significantly increased the number of minor violations with no change in major violations, making them comparable to those of the original AAA plans. Conclusion: The relative difference found between AAA and AXB for SBRT lung plans has been shown to be consistent with previous works. Based on these findings, new guidelines for lung SBRT are recommended when planning with AXB.